2022
DOI: 10.3390/ijms23137081
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Kiteplatin Efficacy by a Benzoato Pt(IV) Prodrug Suitable for Oral Administration

Abstract: Kiteplatin, [PtCl2(cis-1,4-DACH)] (DACH = diaminocyclohexane), contains an isomeric form of the oxaliplatin diamine ligand trans-1R,2R-DACH and has been proposed as a valuable drug candidate against cisplatin- and oxaliplatin-resistant tumors, in particular, colorectal cancer. To further improve the activity of kiteplatin, it has been transformed into a Pt(IV) prodrug by the addition of two benzoato groups in the axial positions. The new compound, cis,trans,cis-[PtCl2(OBz)2(cis-1,4-DACH)] (1; OBz = benzoate), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Inspiring examples were reported by Zhu et al, who brilliantly demonstrated that the anchoring of photoactive molecules such as porphyrins or coumarins to a Pt­(IV) center provided a handle to switch on and enhance the antiproliferative activity of such derivatives. Others reported Pt­(IV) complexes conjugated with bioactive ligands such as drugs, vitamin analogues, enzyme inhibitors, or imaging agents . Also in the case of these dual-action agents, the biological activity strongly depends on the redox chemistry of the Pt ion.…”
Section: Introductionmentioning
confidence: 99%
“…Inspiring examples were reported by Zhu et al, who brilliantly demonstrated that the anchoring of photoactive molecules such as porphyrins or coumarins to a Pt­(IV) center provided a handle to switch on and enhance the antiproliferative activity of such derivatives. Others reported Pt­(IV) complexes conjugated with bioactive ligands such as drugs, vitamin analogues, enzyme inhibitors, or imaging agents . Also in the case of these dual-action agents, the biological activity strongly depends on the redox chemistry of the Pt ion.…”
Section: Introductionmentioning
confidence: 99%
“…Complex 46 was found significantly more effective than cisplatin against A549 cells in vitro with an IC 50 value of 0.05 μM ( Margiotta et al, 2016 ). In vivo anticancer activity of complex 46 after oral administration on LLC-bearing mouse model was comparable with intraperitoneal administration of cisplatin ( Barbanente et al, 2022 ). These results suggest that complex 46 have potential as oral anticancer agents.…”
Section: Dual-stimuli-responsive Pt- and Ru-based Anticancer Drugsmentioning
confidence: 95%
“…Inspiring examples were reported by Zhu who brilliantly demonstrated that anchoring of photoactive molecules such as porphyrins, 13 or coumarins 14 to a Pt(IV) center provided a handle to switch on and enhance the antiproliferative activity of such derivatives. Others reported Pt(IV) complexes conjugated with bioactive ligands such as drugs, [15][16][17][18][19][20] vitamin analogues, 21 enzyme inhibitors [22][23][24] or imaging agents. 25 Also in the case of these dual-action agents, the biological activity strongly depends on the redox chemistry of the Pt ion.…”
Section: Introductionmentioning
confidence: 99%